10.36873/jht.v15i2.2167 PP. 112-120 : Hidayatul Latifah1 , Paulus Matius2 , Rita Diana2 *: POLA SEBARAN SPASIAL JENIS Macaranga gigantea (Rchb.f. & Zoll.) MÃ¼ll.Arg. DI HUTAN PENDIDIKAN FAHUTAN UNMUL (Spatial distribution pattern of Macaranga gigantea (Rchb.f. & Zoll.) MÃ¼ll.Arg. in Fahutan Unmul Forest Education) - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2020)
Macaranga gigantea was one of the pioneer species who started the succession process after the forest fires and grew as dominant species. Therefore, the information on the spatial distribution pattern of M. gigantea is required as necessary data to determine the strategy for managing forest after forest fires. This study aimed to map out of distribution and identified the spatial distribution pattern of M. gigantea. Spatial analysis was to mapping out the location of M. gigantea distribution using remote sensing technology. Vegetation analysis was done by setting up a quadratic method in a square-shaped observation plot in 100 m track and then put into the location of the spread of M. gigantea by a purposive sampling method. The result showed that the spatial pattern of M. gigantea distribution tends to clump. The spatial pattern tends to clumped caused by thesimilarity of life needs between individuals, especially for light. Keywords: Pioneer species, spatial distribution pattern, composition and structure of vegetation